Budget execution of SIS financial transfers and availability of medical supplies in MINSA level III establishments in Lima - Gamarra Mariano, Fiorella Melissa (2024)
Objective: Determine the relationship between the budget execution of financial transfers from the SIS (Seguro Integral de Salud) and the availability of medical supplies in third-level establishments of the Ministry of Health of Metropolitan Lima. Material and method: Analytical and cross-sectional study, carried out in the 20 level III establishments of the MINSA in Lima; Likewise, documentary information was used such as Closing Minutes of Financial Supervision of the Macroregional Management of the SIS from which information on budget execution was obtained and the availability of medical supplies was obtained from the Mundo IPRESS web portal (Institutions Providing Health Services). After evaluating normality with the Shapiro-Wilk test, the Spearman correlation test was used. Result: Overall budget execution was not related to the availability of medical supplies (rho=-0.014; p=0.955). The evaluation by components showed that budget execution on medicines was positively related to the availability of supplies (rho=0.417; p=0.045), which was also valid in the segmented analysis only for hospitals (rho: 0.594; p=0.032). Although budget execution in segmented materials and supplies for hospitals was related to the availability of supplies, this relationship was inverse (rho=-0.552; p=0.043). Conclusions: The general budget execution of financial transfers from the SIS was not related to the availability of medical supplies, but the spending component on medicines was.